Identifikasi Faktor-Faktor Yang Mempengaruhi Kinerja UKM Catering di Kota Bandung - Samir, Alfin; Larso, Dwi (SBM ITB, 2011)
Catering business is general terms for the business that serve various foods and drinks orders include equipment for the needs of party or institution at a certain time and place.The growing demand for catering services causing a large number of new small medium catering enterprises are entering into this area so that makes the high competition among small medium catering enterprises. This condition makes small medium catering enterprises have more challenge in order to maintain their survival. Therefore, it is necessary to identify the factors that influence the performance of small medium catering enterprises in Bandung.This research examines factors that influence small medium catering enterprises performance. These factors include psychological capital of entrepreneurs, human resource management, innovation, entrepreneurial character, and character of small medium catering enterprises.A survey method was used in this study of 97 catering entrepreneurs in Bandung. According to the results, factors influencing small medium catering enterprises performance in Bandung are psychological capital of entrepreneurs and human resource management.The results showed increasing of psychological capital and human resource management will improve small medium catering enterprises performance in Bandung. The results also showed that the most influencing variable toward small medium catering enterprises performance was psychological capital of entrepreneurs that consists of self efficacy, optimism, hope and resiliency.Kata kunci: UKM, catering, kinerja, entrepreneur, modal psikologis, manajemen sumber dayaÂ manusi